Fibrinolysis and Thrombolysis - Kolev, Krasimir (IntechOpen, 2014)
This book familiarizes the reader with some recent trends in the theory and practice of thrombolysis. It covers the field of fibrinolysis from the standpoint of basic scientists and clinicians and delivers the state-of-the-art information on the biochemistry and pharmacology of fibrinolysis, as well as related novel methodological and diagnostic tools in the field. An introductory chapter summarizes the basic molecular mechanisms in fibrinolysis (plasminogen, its endogenous activators and their inhibitors, plasmin and its inhibitors). Recent developments in our understanding of fibrin formation are described in the context of its impact on fibrinolysis. The discussion of neutrophil extracellular traps in the modulation of fibrin assembly and the consequences regarding plasminogen activation and plasmin action addresses a novel aspect of fibrinolysis.